2011
DOI: 10.2478/s13540-011-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a current in a resistor

Abstract: The current in a simple electric circuit consisting of a resistor and a power supply is studied under the assumption that the current starts from zero and reaches its maximum value. It suggests that an evolution process of a current occurs approximating the circuit temporarily to an R-L circuit. The current equation is solved analytically using Mittag-Leffler function. The equation was also solved numerically. Results supported the assumed behavior of current to evolve from zero to its saturation value.MSC 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Consider the electrical series circuit RC with R = 10 O, C = 0:1 F, and V 0 = 10 V. Figure 1(a)-(d) shows numerical simulations for the voltage across the capacitor considering unit step source with bi-order operator, equation (16) and unit step source with ABC operator, equation (24) and periodic source with bi-order operator (27) and periodic source with ABC operator, equation (32), for different particular cases of a and b.…”
Section: Rl Electrical Circuitmentioning
confidence: 99%
“…Consider the electrical series circuit RC with R = 10 O, C = 0:1 F, and V 0 = 10 V. Figure 1(a)-(d) shows numerical simulations for the voltage across the capacitor considering unit step source with bi-order operator, equation (16) and unit step source with ABC operator, equation (24) and periodic source with bi-order operator (27) and periodic source with ABC operator, equation (32), for different particular cases of a and b.…”
Section: Rl Electrical Circuitmentioning
confidence: 99%
“…[11][12][13][14][15]. The use of fractional order operators allows us to generalize the propagation of electrical signals in devices, circuits, and networks [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of this new hybrid circuit without sources has been analyzed [8]. In the work of [9], the simple current sourcewire circuit has been studied fractionally using direct and alternating current source. It was shown that the wire acquires an inducting behavior as the current is initiated in it and gradually recovers its resisting behavior.…”
Section: Introductionmentioning
confidence: 99%